Case Report: Hindlimb Ataxia Concurrent With Seizures by Presumed Osmotic Demyelination Syndrome in a Dog - Lee, Ga-Won; Kang, Min-Hee; Park, Hee-Myung (Frontiers in Veterinary Science, 2022)
A 6-year-old castrated male Chihuahua dog was presented with hindlimb paresis and ataxia. The dog had hyponatremia and was diagnosed as hypoadrenocorticism 10 days before its visit, and the neurologic signs including generalized tonic seizures and hindlimb paresis occurred 3 days after correction of hyponatremia at a referral hospital. Based on history and clinical findings, osmotic demyelination syndrome (ODS) secondary to rapid correction of hyponatremia was highly suspected. After administration of anti-convulsant and supplements, seizures did not occur, and gait was normalized within 2 weeks. Phenobarbital was tapered and finally discontinued after 3 months, and seizure did not recur. The neurologic signs were completely resolved and the dog continued to be free of neurologic or additional clinical signs over the 19-month follow-up period. ODS should be included among the differential diagnoses in case of any acute neurological dysfunction that occurs with episodes of rapid correction of hyponatremia. To the author's knowledge, this is the rare case report of a dog with hypoadrenocorticism and presumed ODS after rapid correction of hyponatremia leading to neurologic signs including seizures and ataxia.